UPAYA MENINGKATKAN HASIL BELAJAR MATEMATIKA MELALUI PENERAPAN MODEL PEMBELAJARAN COOPERATIVE LEARNING TIPE STAD PESERTA DIDIK KELAS IV SD NEGERI SEI ARANG - Mujiyati (Riau Education Journal, 2021)
Â  The research was carried out at SD Negeri 018 Sei Arang using the STAD type cooperative learning model in Mathematics. This research was conducted from March to April in the second semester of 2020. This research was conducted because of the frequent occurrence of problems in the learning process carried out by teachers in planning and implementing the learning process. Therefore, the study took the STAD cooperative learning model with the aim that students in learning were interested in the material. served. The research subjects were fourth grade students of SD Negeri 018 Sei Arang with 26 students. The research procedure was in the form of planning, implementation, observation and reflection. The initial data were the results of the pre-cycle, post-test cycle I and post-test cycle II. the result of learning completeness is 42.30%. While the learning outcomes in the first cycle showed the percentage of learning completeness reached 62% then the post-test learning outcomes in the second cycle the percentage of learning completeness was 80.76%.